Using an inverted funnel analogy to develop a theory of change supporting resilient ecosystem-based adaptation in the Great Lakes Basin: a case study of Lincoln, Ontario, Canada - Liette Vasseur; Bradley May; Meredith Caspell; Alex Marino; Pulkit Garg; Jocelyn Baker; Samantha Gauthier (Canadian Science Publishing, 2022)
Communities in coastal areas of Canada, including the Great Lakes, face a number of challenges, including increased water level variability and extreme weather events, causing flooding and localized erosion. To effectively respond to these coastal risks requires structured, deliberative approaches with the aim of fostering resilience and contributing to sustainability. A collaborative engagement process was used to explore community challenges. This included a project launch, key informant interviews, meetings, focus groups (agriculture, tourism, youth), and on-line methods (shoreline residents). Participatory social network analysis and theory of change were used for overall sense-making. As a result, community members identified six impact pathways moving forward with climate action: partnerships and collaboration; strategic engagement; water and watersheds; ecosystem-based adaptation; shoreline protection; and education. These themes are consistent with current theory on sustainability and theory of change development.